ETL with Azure Cookbook Practical Recipes for Building Modern ETL Solutions to Load and Transform Data from Any Source. - Coté, Christian (Packt Publishing, Limited, 2020)
This book will take you through hand-on recipes for extracting, transforming, and loading data using big data tools and Azure services such as Data Factory and Azure Databricks. You will learn how to interact effectively with Azure services, along with covering automation with BIML and data profiling in Azure.